Varicella-zoster virus necrotising retinitis, retinal vasculitis and panuveitis following uncomplicated chickenpox in an immunocompetent child. (5th April 2018) - Yu, Jonathan; Ashworth, Jane; Hughes, Stephen; Jones, Nicholas
Abstract : A 4-year-old girl presented with acute left visual loss 4 weeks after uneventful chickenpox. She was found to have left necrotising retinitis and profound retinal vasculitis and vitritis. Aqueous humour was PCR positive for varicella-zoster virus. Combined intravenous and intravitreal antiviral treatment led to rapid improvement with settled retinitis, no vascular occlusion and good recovery of vision. Her recent coinfection with Epstein-Barr virus may have acted to provoke the retinitis.